Prinsip Ikrām al-Muslim Gerakan Dakwah Jamaah Tabligh dalam Membangun Masyarakat Religius di Temboro Magetan - Moh Yusuf (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2016)
This article explores the Da'wah Movement of Jamaah Tabligh in building religious community in Temboro Magetan. One one of the main teachings is the principle of Ikrām al-Muslim (honoring and respecting every Muslim). The principle makes the missionary movement acceptable to the Muslim community widely. This principle is really important for the creation of the unity of the Muslims in the name of ukhuwwah Islāmīyah (Islamic brotherhood). This principle prohibits a believer to guestion the religious stream, political choice, position, and social status and background of the individual community of individual Muslims. The principle eventually enables the tabligh community to adapt to different environments and preaching fileds in building religious community. Initially, people did not respond the tabligh mission in Temboro, but it did not dampen the spirit of tablighis to preach. They remain persistent and patient in fighting for the truth of Islam. Their goal is to liven the passion of high religiosity.